Pengaruh Konseling Menyusui Terhadap Cara Menyusui Yang Benar Pada Ibu Post Partum - Ida Yuniarti; Heni Purwaningsih; Sulastri Sulastri (Pusat Riset dan Inovasi Nasional, 2023)
Background: breastfeeding counseling is an effort made by the counselor to the client to help solve a problem that has been experienced by the client without coercion which contains the basics of breastfeeding and knowledge that is very useful for mothers. Objective: To analyze the influence of breastfeeding counseling on the correct way of breastfeeding in post partum mothers. Methodology: Quasi-Experimental research (quasi-experimental). The research design used one-group pretest-posttest, the research was conducted in the Siti Hajar room of RSU Islam Klaten with 30 respondents. The instrument uses a maintenance assessment sheet. The data obtained was then tested for normality using the Shapirro-Wilk test, the data was then processed using the Wilcoxon-Test. Result: the wilcoxon test results showed that the z count was 4.799 greater than the z table, while the p value was 0.000 (p<0.05). Conclusion: There is an influence between breastfeeding counseling on the correct way of breastfeeding at RSU Islam Klaten.